Aerodynamic performance analysis and power generation characteristics experiment of vertical axis wind turbine. Issue 4 (7th February 2022) - Li, Zheng; Liu, Mengjie; Cao, Xin; Gao, Menghai; Cheng, Liyuan; Sun, Hexu
Abstract: With the wide application of clean energy, the requirements of this vertical axis wind turbine are higher and higher. A new diagonal spiral blade vertical axis wind turbine is designed and studied. The shape of the new type of wind turbine blade is designed based on the diagonal spiral structure that is common in life, considering the situation of different pitch angles and constructing 11 kinds of prototype machine. In‐depth analysis of the aerodynamic performance of these new wind turbines through simulation calculations shows that the prototype with a pitch angle of 110° has the best aerodynamic performance. When the tip speed ratio is 0.4, the maximum wind energy utilization rate can reach 0.29. Besides, the model of this wind turbine is constructed by 3D printing, which is tested, and the performance of the models is compared with that of the traditional S‐type wind turbine in a real environment. There rationality and superiority of the design of the new diagonal spiral blade vertical axis wind turbine are proved, and this apply background of this new diagonal spiral blade wind turbine is demonstrated by comparison. This article also analyzes the wake of the wind turbine and makes reasonable planning of the arrangement spacing that the wake effect has the least effect on the downstream wind turbine, which can increase the power generation efficiency of the group arrangement of turbines. Abstract : A new kind of equiangular spiral blade vertical axis wind turbine is designed on the basis of the diagonal spiral. The wind turbine is simply improved by changing the pitch angle, and the 110° pitch angle blade with better performance is selected through the comparison of the simulation calculation method.